Greenhouse gas control technologies : proceedings of the 6th International Conference on Greenhouse Gas Control Technologies, 1-4 October 2002, Kyoto, Japan - Gale, J.; Kaya, Yoichi, 1934- (Pergamon, 2003)
Climate change is an issue that is highly debated around the globe. This book brings together the papers that were presented at a conference dedicated to this issue, held in Kyoto in October 2002. Covering a broad range of areas, the topics presented will benefit both those working in the field of carbon dioxide recovery and sequestration, and those looking at the effects of non carbon dioxide greenhouse gases. An overview of the Research and Design technologies which aid in mitigating climate change is included, which will be invaluable to those researching new opportunities for dealing with this problem. An area of research that has seen a rapid rise in worldwide spend Will benefit both researchers in climate change, and those looking at new technologies to help deal with the problem Presents papers from contributors spread around the globe means that this book has world wide relevance .